Epidemiology of fall and its risk factors among elders in a rural area of Coimbatore, India - Chacko, Thomas V.; Thangaraj, Prabha; G. M., Muhammad (International Journal Of Community Medicine And Public Health, 2017)
Background: Global reports show that falls are the major cause of disability injuries among the elders. Developing countries lack the required epidemiological data on the burden of falls and factors that contribute to it.The objectives of the study were to find the burden of fall and its distribution in time, place and person among elders and to identify risk factors associated with fall among elders. Methods: A community–based cross-sectional study of 655 elders (≥ 60 years) was done in a rural area of Coimbatore District by two stage sampling technique. History of fall within the past 6 months was included in the study. Semi-structured pre-tested questionnaire was used to assess factors contributing to falls. The burden of falls was expressed as proportions and percentages. Logistic regression analysis was done to identify risk factors for fall. Results: 26% (95%CI: 22.59-29.32) elders experienced at least one fall. Of the total falls 50.2% occurred outside home and the remaining inside home. Most of the falls occurred during ambulation and at the morning hours (39.1%). Age ≥80 years (OR: 3.28, 95%CI: 1.28-5.98) and dizziness (OR: 3.27, 95%CI: 1.00-10.06) were only found to be significantly associated with fall on multivariate analysis. Conclusions: The occurrence of fall was found to be almost similar to that identified in western countries where fall preventive measures have been implemented. Similar efforts are yet to be initiated here and so this study provides the evidence for the need. Prospective studies through more frequent home visits are needed to confirm the enormity of the problem to suggest policy recommendation.